Differences in the tooth whitening effect between strawberry juice and apple juice in-vitro - Stephanie, Stephanie; Hayati, Ayu Trisna; Sukartini, Endang (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2012)
Bleaching is the tooth whitening by applying chemical materials oxidizing the organic tooth pigmentation and creating smaller and lighter molecules. Commonly used in the tooth bleaching is hydrogen peroxide. Strawberry and apple contain hydrogen peroxide and ellagic acid which will bond with an unsaturated bond of the tooth pigmentation. The purpose of this research was to finding out and measuring the tooth whitening level and effectivity between the strawberry and apple juice. The type of this research was a true experimental (in-vitro), using 30 samples of maxillary premolars with cutted radicular until the CEJ. Samples were divided into 3 groups (immersed in strawberry juice; apple juice; and mineral water); with three times daily immersion in one week. The tooth colour level was measured using a spectrophotometer. Data were analyzed using the one-way ANOVA and LSD test. The results showed significant differences among all groups. Normality test showed the variance between homogenous groups, with the p-value of 0.198 (p â¥ 0.05). The one-way ANOVA test results showed a significance value (0.000), indicated a significant degree of the tooth whitening level between all groups. The LSD test results showed that the tooth whitening level in group I (immersed in strawberry juice) was significantly different to group II (immersed in apple juice) and group III (immersed in mineral water), with a significance value of 0.01 and 0.00 ( p â¤ 0.05). The tooth whitening level in group II was significantly different from group III, with a significance value of 0.03 (p â¤ 0.05). There were differences in the tooth whitening level between immersion in strawberry juice, apple juice, and mineral water, with the most effective tooth whitening level found in the strawberry juice immersion.